Selangor state structure plan (SSP) : a way forward to 2035 - Kadar Hamsa, Abdul Azeez; Ibrahim, Mansor; Ahmad Sarkawi, Azila; Zen, Irina Safitri; Bajrai, Aaliyah; Ariffuddin, Ahmad; Ikram, Ahmad Zul (2020)
StateStructurePlan(SSP) is a document that prepare a planning framework that will guide and control the state’s physical development as required under the Town and Country Planing Act1976 (Act172). The study area is the Selangor State, located on the west coast of Peninsular Malaysia. This study adopts the process of state structure plan preparation in accordance to Plan Malaysia’s Manual. The development concept proposed in the plan is “Interdependent Polycentric Economic Region”, defined as economic corridor and growth centres that are depending on one and another. There are 5 development thrusts with 32 policies that are being proposed. From the policies, a total of 9 high impact projects being proposed for the state of Selangor.